Android Based Door Security Design - Ruth Shyintia Rouli Marpaung (Brilliance: Research of Artificial Intelligence, 2022)
Room insecurity such as cases of theft or fire can occur, especially in rooms that are not equipped with special security and guard systems. Based on this, it is necessary to develop a security system that can be accessed and monitored remotely and provides early warning of early indications of danger using smartphones. System development is carried out through the stages of making software and hardware. The hardware consists of Arduino Mega 2560 to manage the system, MySQL Database Server, CC3000 Wifi Shield as a communication device between Arduino and the server, Limit Switch to detect a forced push on the door, MQ-2 measuring gas leaks in the room, DHT-11 sensor to measure the room temperature, VC0706 camera to capture images in the door area. Android application as a system interface to change lock status and monitor room conditions. A warning notification of the danger indication of a gas leak is sent to the user's smartphone by displaying the value of the gas content. The warning message of a forced push on the door is equipped with a feature to display camera captures. The final result of this research is that a room security system has been successfully created where access to door locks and room monitoring can be done through an android application installed on a smartphone. The system can provide a hazard warning message well. The warning message of a forced push on the door is equipped with a feature to display camera captures. The final result of this research is that a room security system has been successfully created where access to door locks and room monitoring can be done through an android application installed on a smartphone. The system can provide a hazard warning message well. The warning message of a forced push on the door is equipped with a feature to display camera captures. The final result of this research is that a room security system has been successfully created where access to door locks and room monitoring can be done through an android application installed on a smartphone. The system can provide a hazard warning message well.